The Timing of Growth Promotion and Conversion to Indole-3-acetic Acid for Auxin Precursors - Evans, Michael L. (1970)
Using a high resolution continuous recording technique, the length of the latent period preceding the growth response to two suspected precursors of indole-3-acetic acid (IAA) indole-3-acetonitrile (IAN), and indole-3-ethanol was studied in corn (Zea mays L.), wheat (Triticum aestivum L.), and peas (Pisum sativum L.). The timing of the conversion in vivo of these presumed precursors to IAA was also examined. In wheat the rate of conversion of IAN to IAA is rapid, and the latent period in the growth response to IAN is correspondingly short. In corn the rate of conversion in vivo of IAN to IAA is slow, and there is a long latent period in the growth response. In peas there is no conversion of IAN to IAA, and there is no measurable growth response to IAN. These data indicate that IAN is active in promoting growth only after conversion to IAA. This conclusion is strengthened by transport studies. Using a similar approach, we have also obtained data indicating that indole-3-ethanol is active only after conversion to IAA.